AN ERROR ANALYSIS IN USING SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE TEXT BY THE EIGHTH GRADE STUDENTS OF SMP HANG TUAH MANADO - Nur Halimah; Nikmala Nemin Kaharuddin; Vivi Dyah Rahmawati (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research aimed to analyze students’ errors in using simple present tense especially in the use of verb be and verb in writing descriptive text. The writer focuses on one of error classification by Dulay namely misformation. The research methodology was descriptive qualitative method. The informants of this research were the eighth grade students of VIII A which consisted of 32 students in SMP Hang Tuah Manado the technique of analyzing the data was evaluated with error analysis. The data were derived from test instrument which conducted with the following procedures of error analysis. The first procedure was collecting the sample of students to provide the data obtained by giving a test containing of simple present tense (verb be and verb), the second procedure was identifying the error based on the test, the third was describing the error, the fourth was explaining the error and the last evaluating the error. The result of this research indicate that the total errorscommittedly 32 students were 329 out of 655 items with 46.84%. The use of verb be and verb in simple present tense that contains the most error is verb with 169 by47.98%. It is followed by the use verb be with 160 frequency and percentage of error like 45.70%.